UW Project ECHO‐Dementia: Implementation of a virtual clinic and telementoring program to improve dementia diagnosis and treatment in rural and under‐resourced primary care settings. (31st December 2021) - Rhoads, Kristoffer; Isenberg, Nancy; Schrier, Allyson
Abstract: Background: Primary care providers are on the front lines of dementia care and frequently the first point of contact for individuals and families concerned about changes in memory and thinking. In addition to the challenges of managing complex medical comorbidities, primary care providers in rural or lower‐resource settings often lack access to specialists, interdisciplinary teams or other programs and services to aid in diagnosis and care of individuals with mild cognitive impairment and dementia. The current project extends an existing technology‐based hub and spoke model virtual clinic, Project ECHO (Extension for Community Healthcare Outcomes, University of New Mexico), to improve diagnosis and care of dementia in primary care. Method: The current project is an extension of work related to the Washington State Plan for Alzheimer's Disease and Other Dementias with implementation supported by legislative funding. The program includes an interdisciplinary expert panel ("hub") meeting with participants ("spokes") including primary and allied health care providers from healthcare systems, group practices, and solo practitioners. The twice‐monthly virtual clinic sessions include a brief didactic followed by case‐based learning in an "all‐teach, all‐learn" format emphasizing expertise and experience of spoke sites as well as the hub. Participants are provided with resources discussed during the clinic session, ongoing opportunities for consultation, and free continuing education credits. Results: Launching amid the COVID‐19 pandemic, the program has provided over 250 hours of education to more than 50 providers across 20 unique sites. Post session surveys indicate that the program is well‐received with 2 in 3 providers indicating that they will change their practice based on learning. Surveys also demonstrate significant increases in both knowledge and confidence in dementia‐specific diagnosis and care. Conclusion: The success of the current project demonstrates both the feasibility and benefit of leveraging technology to deliver dementia‐related education to primary care providers in rural and under‐resourced settings. While initially hampered by disruptions in care due to the COVID‐19 pandemic, increased technological proficiency on the provider and systems level has appeared to be a benefit in terms of resources and comfort participating in a virtual education program to scale Dementia Capable Care in Primary Care.